1993
DOI: 10.1002/eji.1830231243
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐presenting human T cells and antigen‐presenting B cells induce a similar cytokine profile in specific T cell clones

Abstract: One of the factors that may influence the cytokine secretion profile of a T cell is the antigen-presenting cell (APC). Since activated human T cells have been described to express major histocompatibility complex (MHC) class II molecules as well as costimulatory molecules for T cell activation, like e.g. ICAM-1, LFA-3 and B7, they might play a role as APC and be involved in the regulation of T-Tcell interactions. To define further the role of T cells as APC we tested their capacity to induce proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
(14 reference statements)
2
21
0
Order By: Relevance
“…Epstein-Barr virus-transformed (EBV-transformed) B-lymphoblastoid cell lines (B-LCLs) were generated as described (29) and cultured in RPMI-1640 supplemented with 10% FCS, 25 mM HEPES buffer, but without L-glutamine and without antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Epstein-Barr virus-transformed (EBV-transformed) B-lymphoblastoid cell lines (B-LCLs) were generated as described (29) and cultured in RPMI-1640 supplemented with 10% FCS, 25 mM HEPES buffer, but without L-glutamine and without antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…The medium for culture of EBV-transformed B lymphoblastoid cell lines (B-LCL) was RPMI 1640 supplemented with 10% heat-inactivated FCS (Gibco, Paisley, UK), 25 mM Hepes buffer, but no L -glutamine and no antibiotics. B-LCL were generated as described (23).…”
Section: Methodsmentioning
confidence: 99%
“…Thus to determine whether the T M established by adoptive transfer could respond to antigen stimulation in vivo, we infused autologous T cells pulsed with CMV IE peptide (forming antigen-presenting T cells [T-APC]). We chose to use T-APCs because these cells could be easily prepared and prior human studies have shown that T cells expressing a foreign antigen can boost antigen-specific T M responses in vitro and in vivo (32,33). Peptide-pulsed T-APCs were lysed by the CMV-specific T cell clone in vitro ( Figure 8A) and were infused to macaque A99171 nine weeks after transfer of the CD19 + T CM -derived clone.…”
Section: Figurementioning
confidence: 99%